REPRESENTING RELIGION AND GENDER STEREOTYPES IN HOMEIRA QADERI’S DANCING IN THE MOSQUE (2020) - Noria Mohammadi; Mohammad Ibrahim Paracha (Adabiyyāt: Jurnal Bahasa dan Sastra, 2025)
This study examines how religion contributes to the construction of gender stereotypes in Afghan society as represented in Homeira Qaderi’s memoir Dancing in the Mosque (2020). The memoir illustrates how patriarchal norms legitimized through religious discourse restrict women’s education, autonomy, and social participation. To analyze this issue, the research applies Susan Lanser’s feminist narratology, which emphasizes the mimetic function of narrative and its connection to lived reality. Through a close reading of narrative elements such as voice, focalization, and symbolic space, the study demonstrates that religion is often instrumentalized to justify cultural practices that sustain gender inequality. At the same time, Qaderi’s act of storytelling functions as a form of resistance, breaking silences, and challenging patriarchal authority by amplifying women’s voices. These findings show that feminist narratology provides an effective framework for linking narrative structures to the realities of Afghan women’s lives. The research underscores the importance of literature in exposing oppression, strengthening feminist critique, and contributing to the discourse on social change.